SPONTANEOUS PNEUMOTHORAX IN A TERM NEONATE: A CASE REPORT - Momen Gharibvand, Mohammad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Spontaneous pneumothorax does not occur frequently in the newborn. The prevalence of spontaneous neonatal pneumothorax is twice in male as in female neonates. It should be suspected in any neonate with respiratory distress. In this article, we present a 2.6 kg term male neonate who developed respiratory distress 14 h after birth. An urgent chest X-ray anteroposterior was ordered for evaluation. Chest X-ray revealed a left-sided pneumothorax along with mediastinal and tracheal shift to the opposite side which was suggestive of tension pneumothorax. If considerable distress persists, continuous drainage of the pneumothorax should be provided by means of an intercostal drainage and an underwater seal.